Vale(rivs) Pate(rnvs). Análisis cronotipológico y antroponímico de una officina productora de terra sigillata hispánica - Bustamante-Álvarez, Macarena; Simón Cornago, Ignacio (Rei Cretariae Romanae Fautorum Acta, 2023)
A comprehensive analysis of the epigraphic stamps of the potter Vale(rius) Pate(rnus) on Hispanic samian ware is presented. This potter is characterized by being one of the most prolific in Hispanic production due to its large number of specimens located on soil, not only on the peninsula. Mainly, to address this analysis, we use all the stamps located in the ancient province of Lusitania collected by the CVH research project. In addition to a typological, medium or contextual analysis of these findings, we present a proposal for epigraphic and anthroponymic characterization that allows us to develop hypotheses about this fruitful officina.